Influence of hydrochloric acid against food-grade steel SUS304 and its corrosion impact / Nur Dhiya Syariah Mazelam ... [et al.] - Mazelam, Nur Dhiya Syariah; Yahya, Solhan; Ab. Ghani, Zaidi; Ahmad, Zuliahani; Samsudin, Dalina; Muhd Zailani, Nabilah Akemal (UiTM Cawangan Negeri Sembilan, 2022)
This study aims to investigate the progress of corrosion rate on stainless steel (SUS304) in hydrochloric acid (HCl) as exposed for 8 days. The HCl as a corrosive medium was used at pH 2 and pH 5. The evaluation of corrosion rate was done through weight loss measurement. Morphology and structure of metal specimens were characterized by optical microscope before and after immersion test. The results showed that the corrosion rates were increased significantly within 4 days of immersion. The corrosion rate in pH 2 reveals the highest values at 0.020 mm/y. While in pH 5, the rate of corrosion exhibits moderate value ranging from 0.006-0.011 mm/y. The corrosion behavior of the stainless steel coupon was influenced by the duration of exposure in the HCl medium. The concentration of hydrogen cations and aggressiveness of chloride anion in the corrosive medium has been associated with corrosion.